Hubungan Umur dan Tingkat Pengetahuan Ibu Nifas tentang KB dengan Keikutsertaan KB Pascasalin di Wilayah Kerja UPT Puskesmas Bajayau - Rini Wahyuni; Ika Friscila; Anita Herawati; Aida Fitriani (Universitas Malahayati Lampung, 2025)
ABSTRACT Postpartum birth control participation in postpartum mothers is important because the return of fertility in a mother after childbirth is unpredictable and can occur before the arrival of the menstrual cycle, even in breastfeeding mothers. Postpartum birth control has the goal of maintaining pregnancy spacing, regulating childbirth and avoiding unwanted pregnancies. The purpose of this study was to determine the relationship between the age and level of knowledge of postpartum mothers about family planning with postpartum family planning participation in the work area of UPT Puskesmas Bajayau. This research method uses a quantitative approach with the crossectiona method. The population is 109 people. The whole mother is puerperal. Simple random sampling technique as many as 57 people. Questionnaire collection technique. Data analysis using descriptive analysis and statistical chi-square test analysis. The age of the most postpartum mothers who were respondents was the age of 20-35 years as many as 30 people, the level of knowledge of postpartum mothers was mostly included in the category of less than 34 people, postpartum mothers who participated in postpartum birth control only amounted to 25 people, there was an age relationship with the participation of postpartum family planning in the Working Area of UPT Puskesmas Bajayau in 2022 (p. value 0.05) with a significant value (p) result of 0.000. There is a relationship between the level of knowledge of postpartum mothers about family planning with the participation of postpartum family planning in the Bajayau Health Center Work Unit in 2022 (p. value 0.05) with a significant value (p) of 0.000. That the age and level of knowledge of postpartum mothers are related to the participation of postpartum birth control. Keywords: Postpartum Mother, Participation, Postpartum Birth Control, Knowledge, Age ABSTRAK Keikutsertaan KB Pasca Salin pada ibu nifas penting karena kembalinya kesuburan pada seorang ibu setelah melahirkan tidak dapat diprediksi dan dapat terjadi sebelum datangnya siklus haid, bahkan pada ibu menyusui. KB Pasca persalinan mempunyai tujuan yaitu menjaga jarak kehamilan, mengatur kelahiran dan menghindari kehamilan yang tidak diinginkan. Mengetahui hubungan umur dan tingkat pengetahuan ibu nifas tentang KB dengan keikutsertaan KB Pascasalin Di Wilayah Kerja UPT Puskesmas Bajayau. Metode penelitian ini menggunakan pendekatan kuantitatif dengan metode crossectional. Populasi sebanyak 109 jiwa orang. Seluruh ibu nifas. Teknik pengambilan sampel Simple random sampling sebanyak 57 Orang. Teknik pengumulan kuesioner. Analisis data menggunakan analisis deskriptif dan analisis uji statistic chi-square. Umur ibu nifas terbanyak yang menjadi responden adalah umur 20-35 tahun sebanyak 30 orang, tingkat pengetahuan ibu nifas sebagian besar termasuk kategori kurang sebanyak 34 orang, ibu nifas yang mengikuti KB pascasalin hanya berjumlah 25 orang, ada hubungan umur dengan Keikutsertaan KB Pascasalin di Wilayah Kerja UPT Puskesmas Bajayau Tahun 2022 (p. value 0,05) dengan hasil nilai signifikan (p) 0,000. Ada hubungan tingkat pengetahuan ibu nifas tentang KB dengan Keikutsertaan KB Pascasalin di Wilayah UPT Kerja Puskesmas Bajayau Tahun 2022 (p. value 0,05) dengan hasil nilai signifikan (p) 0,000. Bahwa umur dan tingkat pengetahuan ibu nifas berhubungan dengan keikutsertaan KB Pascasalin. Kata Kunci: Ibu Nifas, Keikutsertaan, Kb Pascasalin, Pengetahuan, Umur